Combination of Moringa Leaf Meal and Probiotics in Feed for Tilapia (Oreochromis niloticus) Seeds Survival and Immune System - Fariq Azhar; Nanang Satria Sumarjan; Siti Hilyana (Department of Aquaculture, 2021)
Prevention of disease in tilapia seeds can be done by increasing non-specific defense systems by improving and supplementing the nutritional content of the feed. This study aims to determine the effect of adding Moringa leaf meal combined with probiotics to feed on the survival rate of tilapia seeds and the number of seed blood cells that have been infected with Aeromonas hydrophila. The method used was an experimental method using a Completely Randomized Design (CRD) with 5 treatments and 3 replications. Treatment A = addition of 4% moringa leaf meal + 6 ml / kg of probiotic feed + A. hydrophila injection; Treatment B = addition of 6% moringa leaf meal + 6 ml / kg of probiotic feed + A. hydrophila injection; Treatment C = addition of 8% moringa leaf meal + 6 ml / kg of probiotic feed + A. hydrophila injection; Treatment D = feed + probiotic 6 ml / kg of feed (positive control) + injection of A. hydrophila; Treatment E = feed + probiotic 6 ml / kg of feed (negative control) + injection of physiological solution. The results showed the addition of Moringa leaf meal combined with probiotics got the best results in treatment C with a survival value of 86.67%, hemoglobin levels of 2.3 g%, erythrocytes of 2.20 × 106 cells, leukocytes of 11.5 × 104 cells, and the total number of intestinal bacteria was 10.34 × 106 cfu / ml.